2020
DOI: 10.1556/650.2020.31665
|View full text |Cite
|
Sign up to set email alerts
|

Szérumbiomarkerek akut lumbalis-lumbosacralis fájdalomban

Abstract: Absztrakt: A porckorongsérvhez és a gerincoszlop egyéb degeneratív elváltozásaihoz társuló lumbalis-lumbosacralis fájdalom patogenezisében szerepet játszik a gyulladás, és feltételezhető, hogy ilyen esetekben egyes gyulladásos mediátorok szintje mérhetően megemelkedik a vérben. A vérben mérhető pro- és antiinflammatorikus citokinek, kemokinek, egyéb szabályozómolekulák és a lumbalis-lumbosacralis fájdal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Moreover, Stover et al [56] suggested the need for targeting of IL-6, TNF-α, and IL-1β for pain modulation in degenerative intervertebral discs and multiple clinical trials evaluated the efficacy of TNF-α and IL-6 inhibitors in treating CBP. [57]…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Stover et al [56] suggested the need for targeting of IL-6, TNF-α, and IL-1β for pain modulation in degenerative intervertebral discs and multiple clinical trials evaluated the efficacy of TNF-α and IL-6 inhibitors in treating CBP. [57]…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have shown promising results with the use of TNF-α inhibitors and IL-6 inhibitors for treating low back pain and sciatica. 3 The currently acknowledged initiating factors of intervertebral disc degeneration (IDD) encompass oxidative stress, aging, nutritional deficiencies, genetic susceptibility and mechanical overload. 4 However, Wang et al have discovered that early degenerative intervertebral discs (IVDs) contain a significant amount of inflammatory factors, primarily including IL-1β, TNF, and IL-18.…”
Section: Introductionmentioning
confidence: 99%